Estudo do comportamento atérmico no sistema vítreo fosfato PANK em função da razão K2O/Al2O3 - Silva Filho, José Carlos (2021)
A large number of vitreous systems have been studied in recent years from the combination of different oxides in order to obtain a host matrix of rare-earth ions to be applied as an active laser medium. Among these systems, phosphate glasses stand out, which are known to have the ability to be athermal, since they exhibit a negative thermo-optical coefficient that opposes the thermal expansion of the material. The athermal behavior eliminates optical distortions in the material that is essential for high average power lasers where an increase in material temperature occurs. Thus, the purpose of this thesis is to investigate the origin of the athermal behavior in the phosphate glass matrix P2O5-Al2O3-Na2O-K2O close to 180 K, to verify if this athermal effect can be shifted to room temperature and to show that the thermal lens technique is the most suitable for observing the athermal effect. Using a double single-arm interferometer, it was possible to obtain simultaneously the thermal expansion coefficient (α) and the thermo-optical coefficient (dn/dT) as a function of temperature. It was verified, through the interference pattern, that close to the athermal region of the material, the fringe period is long, and this indicates a change in its direction with temperature. From this result, a procedure to obtain the parameters α and dn/dT through the phase derivative of the interference pattern was proposed. Furthermore, changing the K2O/Al2O3 ratio of the vitreous system, it was shown that the athermal effect was shifted to room temperature using the thermal lens technique, which also allowed us to assume that the sample with K2O/Al2O3 ~ 9 is athermal at room temperature.